2019
DOI: 10.1080/10942912.2019.1628779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various magnesium salts for the production of milk fermented by Bifidobacterium animalis ssp. lactis Bb-12

Abstract: The aim of this work was to develop of functional dairy product fortified with magnesium and contained probiotic bacteria Bifidobacterium Bb-12. Therefore, the effect of various magnesium salts on physicochemical, organoleptic and texture properties and Bifidobacterium Bb-12 survival were assessed. The best stimulator of bacterial growth was D-gluconate. Although the addition of L-lactate and acetate decreased the growth rate of showed a positive effect on bacterial survival. The fortification with magnesium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
3
0
5
Order By: Relevance
“…A higher addition of this magnesium salt presumably increased significantly the dry matter content and a hardness of gel. According to Szajnar et al [42] the introduction of various magnesium salts could affect the ability of the strain to produce EPS, which can explain differences in the hardness of the samples tested. Earlier studies showed that the addition of calcium chloride to goat's milk also increased the hardness of yoghurts.…”
Section: Parameters Of Texturementioning
confidence: 99%
“…A higher addition of this magnesium salt presumably increased significantly the dry matter content and a hardness of gel. According to Szajnar et al [42] the introduction of various magnesium salts could affect the ability of the strain to produce EPS, which can explain differences in the hardness of the samples tested. Earlier studies showed that the addition of calcium chloride to goat's milk also increased the hardness of yoghurts.…”
Section: Parameters Of Texturementioning
confidence: 99%
“…Syneresis was measured as the amount of whey released relative to the initial weight and averaged five determinations. The 10 g of fermented milk sample was transferred into 50 mL plastic tube and centrifuged Refrigerated Centrifuge LMC-4200R (Biosan SIA, Riga, Latvia) [ 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…W badaniach Szajnar i wsp. [15] rodzaj wprowadzonego do mleka krowiego związku magnezu nie różnicował istotnie wartości pH i zawartości kwasu mlekowego.…”
Section: Wyniki I Dyskusjaunclassified
“…Odmienne wyniki odnotowały natomiast Szajnar i wsp. [15] wnioskując, że dodatek D-glukonianu magnezu do mleka krowiego obniżył podatność jogurtów na wydzielanie serwatki o ok. 20 %. Synereza jest znacząco uzależniona od rodzaju kultury starterowej stosowanej do fermentacji mleka ze względu na wytwarzane metabolity, w tym egzopolisacharydy, które mają zdolność wiązania wody wolnej i modyfikacji żelu jogurtowego podczas procesu koagulacji [6].…”
Section: Wyniki I Dyskusjaunclassified